2001
DOI: 10.1182/blood.v97.10.3251
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide 3-kinase modulation of β3-integrin represents an endogenous “braking” mechanism during neutrophil transmatrix migration

Abstract: During episodes of inflammation, neutrophils (polymorphonuclear leukocytes[PMNs]) encounter subendothelial matrix substrates that may require additional signaling pathways as directives for movement through the extracellular space. Using an in vitro endothelial and epithelial model, inhibitors of phosphoinositide 3-kinase (PI3K) were observed to promote chemoattractant-stimulated migration by as much as 8 ؎ 0.3-fold. Subsequent studies indicated that PMNs respond in a similar manner to RGD-containing matrix su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 50 publications
2
39
1
Order By: Relevance
“…Although the Syk inhibitor piceatannol blocks RGDinduced phosphorylation of ␤ 3 , it is unlikely that this is the mechanism whereby piceatannol inhibits ␣ v ␤ 3 -mediated adhesion to Fn, because this event is independent of ␤ 3 -tyrosine phosphorylation and yet inhibited by piceatannol. In contrast to another report, we find that wortmannin has no effect on RGD-induced ␤ 3 -tyrosine phosphorylation, and therefore, its inhibitory effects are likely due to inhibition of the increase in PI3K activity and/or the translocation of PI3K to the integrin complex (22). Furthermore, we do not find an effect of wortmannin on the RGD-induced conformational change of ␣ v ␤ 3 (23).…”
Section: Discussioncontrasting
confidence: 56%
“…Although the Syk inhibitor piceatannol blocks RGDinduced phosphorylation of ␤ 3 , it is unlikely that this is the mechanism whereby piceatannol inhibits ␣ v ␤ 3 -mediated adhesion to Fn, because this event is independent of ␤ 3 -tyrosine phosphorylation and yet inhibited by piceatannol. In contrast to another report, we find that wortmannin has no effect on RGD-induced ␤ 3 -tyrosine phosphorylation, and therefore, its inhibitory effects are likely due to inhibition of the increase in PI3K activity and/or the translocation of PI3K to the integrin complex (22). Furthermore, we do not find an effect of wortmannin on the RGD-induced conformational change of ␣ v ␤ 3 (23).…”
Section: Discussioncontrasting
confidence: 56%
“…We chose to study this interaction because fibronectin is an extracellular matrix component involved in enhancing survival of hematopoietic cells (5). Interaction with fibronectin is also implicated in phagocyte rolling (8). In these studies, we found that 48 h of IFN␥ differentiation significantly increased U937 cell adhesion to fibronectin (p Ͻ 0.03, n ϭ 4) (Fig.…”
Section: Resultsmentioning
confidence: 51%
“…We also investigated activation of Syk protein-tyrosine kinase, a downstream target of ␤3 integrin that mediates cell survival signals (8). For these studies, the blots were serially probed with antibodies to phosphorylated (activated) and total Syk.…”
Section: Hoxa10 Expression Influenced ␤3 Integrin Expression and Fibrmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, inhibitor experiments examining the role of PI3K in PMN chemotaxis have yielded conflicting results. In particular, some reports on treatment of PMN with either wortmannin or LY294002 have shown only minimal inhibitory effects on PMN chemotaxis toward fMLP by under agarose assays (45), whereas others have observed enhanced PMN chemotaxis in Transwell migration assays in the presence of the same inhibitors (31,51). Roles for other PI3Ks in PMN migration have also been inferred.…”
Section: Signaling Pathways That Regulate Leukocyte Migrationmentioning
confidence: 99%